A twenty-year review of diagnosing and treating children with diffuse intrinsic pontine glioma in The Netherlands. Issue 2 (February 2014) - Veldhuijzen van Zanten, Sophie EM; Jansen, Marc HA; Sanchez Aliaga, Esther; van Vuurden, Dannis G; Vandertop, W Peter; Kaspers, Gertjan JL
<x xml:space="preserve">Abstract</x> Introduction: Children with diffuse intrinsic pontine glioma (DIPG) face a dismal prognosis, with a median overall survival of 9 months. Our aims are to determine the incidence of DIPG in the Netherlands and to identify points for improvement in clinical research, a prerequisite for increasing the chance to find a cure. Methods: We performed a population-based retrospective cohort study by evaluating all children diagnosed with DIPG in the Netherlands between 1990 and 2010. Results: The incidence of DIPG in the Netherlands corresponds with international literature. Between 1990 and 2010, a large heterogeneity of treatment schedules was applied and only a minority of patients was included in clinical trials. Discussion: Given the rarity of DIPG, we emphasize the need for (inter-)national trials to facilitate the identification of potentially effective therapeutics in the future. This can be supported by the recent development of a European DIPG registry enabling international study collaborations.